Comprehensive textbook of AIDS psychiatry - Cohen, Mary Ann, 1941-; Gorman, Jack M. (Oxford University Press, 2008)
Among the vast and rapidly growing field of AIDS research, there is an ample body of evidence supporting the fact that psychiatric treatment can decrease transmission, diminish suffering, improve adherence, and decrease morbidity and mortality. There is probably no other illness in which the connections between mind and body are so inextricably woven. But until now there has been no comprehensive textbook of AIDS psychiatry to guide clinicians towards providing much needed care. Using a biopsychosocial approach, this 41-chapter volume offers insight into the interface between the psychiatric.